2008
DOI: 10.1007/s00204-008-0381-z
|View full text |Cite
|
Sign up to set email alerts
|

Synergism of aromatic amines and benzo[a]pyrene in induction of Ah receptor-dependent genes

Abstract: Aromatic amines have been shown to cause bladder cancer. However, epithelial cells of the urinary bladder, cells of origin of bladder cancer, may be exposed to numerous substances besides aromatic amines. In the present study, we analysed possible interactions between the aromatic amines 4-aminobiphenyl (4-ABP) as well as 2-naphthylamine (2-NA) and the polycyclic aromatic hydrocarbon benzo[a]pyrene (B[a]P). For this purpose we incubated primary porcine urinary bladder epithelial cells (PUBEC) with concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…It has already been reported that benzo[ g,h ,i]perylene increased the B[a]P‐mediated CYP1A1 transcription in HepG2 cells as well as B[a]P DNA adducts (Cherng et al, ). Similarly, some aromatic amines were shown to interact synergistically with B(a)P in the transcription of Ah receptor‐dependent genes (Borza et al, ). It is worthwhile to point out that 1‐MP, which failed to interact with B(a)P, is not a ligand for this receptor, whereas B(b)F, the only compound that antagonized B(a)P in the present study, is also the only PAH that has higher affinity than B(a)P for this receptor (Pushparajah et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It has already been reported that benzo[ g,h ,i]perylene increased the B[a]P‐mediated CYP1A1 transcription in HepG2 cells as well as B[a]P DNA adducts (Cherng et al, ). Similarly, some aromatic amines were shown to interact synergistically with B(a)P in the transcription of Ah receptor‐dependent genes (Borza et al, ). It is worthwhile to point out that 1‐MP, which failed to interact with B(a)P, is not a ligand for this receptor, whereas B(b)F, the only compound that antagonized B(a)P in the present study, is also the only PAH that has higher affinity than B(a)P for this receptor (Pushparajah et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…genes through the activation of AhR (Borza et al 2008;Dumont et al 2010). 2-NA and 4-ABP have been shown to induce CYP1A1 in PUBEC cells (Borza et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Certain aromatic amides (N-acetyl-AA) such as 2-acetylaminofluorene (2-AAF) and 2-acetylaminophenanthrene (2-AAP) have been reported to bind to the rat AhR (Cikryt et al 1990). Interestingly, a higher induction of CYP1A genes was observed (Borza et al 2008) when porcine urinary bladder epithelial cells (PUBEC) were co-exposed to B(a)P in combination with 4-ABP or 2-NA (as compared to B(a)P). However, these AAs did not induce the expression of CYP1A in the absence of B(a)P. In addition, some AhR target genes, including CYP1A1 and CYP1A2, are strongly regulated in response to acute and chronic exposure to heterocyclic aromatic amines (HAA) (Dumont et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Having this in mind, Borza et al (2008) studied the interaction between the aromatic amine 4-aminobiphenyl (1-50 µM) and benzo[a]pyrene (1 µM) in the PUBEC model. As expected, benzo[a]pyrene increased mrNA expression of CYP1A1, whereas 4-aminobiphenyl alone had no such effect.…”
Section: ) and Tobacco Smokementioning
confidence: 99%